A fuzzy multiple criteria comparison of technology valuation methods for the new materials development - Cheng, An-Chin (Technological and Economic Development of Economy, 2013)
New materials have been recognized as key drivers for corporate profitability and growth in today's fast changing environment. To evaluate the development and gain useful appraising information of new materials thus becomes a critical issue. However, little has been done in discussing the selection of technology valuation methods for the development of new materials. Accordingly, this study adopted the fuzzy AHP method to obtain the opinions of professionals on this issue. These efforts resulted in seven evaluation criteria with one, the “data validity” being given the highest weight, followed by “method adaptability” and “technology development evaluability”. It was concluded that the real option approach and income method are the two most applicable technology valuation methods for evaluating new materials development. In addition, the application of the fuzzy AHP method provided a relevant avenue for corporation policy makers and researchers to evaluate the technology valuation methods for new materials.